Data Gaps, Data Incomparability, and Data Imputation : A Review of Poverty Measurement Methods for Data-Scarce Environments - Dang, Hai-Anh; Jolliffe, Dean; Carletto, Calogero (World Bank, Washington, DC, 2017)
This paper reviews methods that have been employed to estimate poverty in contexts where household consumption data are unavailable or missing. These contexts range from completely missing and partially missing consumption data in cross-sectional household surveys, to missing panel household data. The paper focuses on methods that aim to compare trends and dynamic patterns of poverty outcomes over time. It presents the various methods under a common framework, with pedagogical discussion on the intuition. Empirical illustrations are provided using several rounds of household survey data from Vietnam. Furthermore, the paper provides a practical guide with detailed instructions on computer programs that can be used to implement the reviewed techniques.